Effectiveness of the Euvichol® oral cholera vaccine at 2 years: A case-control and bias-indicator study in Haiti - Wilfredo R. Matias; Yodeline Guillaume; Gertrude Cene Augustin; Kenia Vissieres; Ralph Ternier; Damien M. Slater; Jason B. Harris; Molly F. Franke; Louise C. Ivers (International Journal of Infectious Diseases, 2024)
Objectives: The World Health Organization recommends the use of oral cholera vaccine (OCV) in cholera control efforts. Euvichol®, pre-qualified in 2015, is the leading component of the Global OCV stockpile, but data on its field effectiveness are limited. To evaluate Euvichol® vaccine effectiveness (VE), we conducted a case-control study between September 2018 to March 2020 following an OCV campaign in November 2017 in Haiti. Methods: Cases were individuals with acute watery diarrhea. Stool samples were tested by culture and real-time polymerase chain reaction of the Vibrio cholerae ctxA gene. Cases were matched to four community controls without diarrhea by residence, enrollment time, age, and gender, and interviewed for sociodemographics, risk factors, and self-reported vaccination. Cholera cases were analyzed by conditional logistic regression in the VE study. Non-cholera diarrhea cases were analyzed in a bias-indicator study. Results: We enrolled 15 cholera cases matched to 60 controls, and 63 non-cholera diarrhea cases matched to 249 controls. In the VE analysis, eight (53%) cases reported vaccination with any number of doses compared to 43 (72%) controls. Adjusted two-dose OCV VE was 69% (95% CI –71 to 94%). Conclusions: Between 10-27 months after vaccination, Euvichol® was effective and similar to Shanchol™, suggesting that it can serve as one component of multi-sectoral comprehensive cholera control.